2013
DOI: 10.2147/dddt.s48636
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of mutual azo prodrug of 5-aminosalicylic acid linked to 2-phenylbenzoxazole-2-yl-5-acetic acid in ulcerative colitis

Abstract: In this study, the syntheses of 4-aminophenylbenzoxazol-2-yl-5-acetic acid, (an analogue of a known nonsteroidal anti-inflammatory drug [NSAID]) and 5-[4-(benzoxazol-2-yl-5-acetic acid)phenylazo]-2-hydroxybenzoic acid (a novel mutual azo prodrug of 5-aminosalicylic acid [5-ASA]) are reported. The structures of the synthesized compounds were confirmed using infrared (IR), hydrogen-1 nuclear magnetic resonance (1H NMR), and mass spectrometry (MS) spectroscopy. Incubation of the azo compound with rat cecal conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…It was reported that more than 30 commonly prescribed drugs were metabolically altered by the enzymes in gut microbiota 24 , 25 , 26 , including methylase/demethylase, β -glucuronidase, nitroreductase, azoreductase, and so on 27 , 28 , 29 , 30 , 31 . For example, sulfasalazine, a sulfa drug used for the treatment of ulcerative colitis, is absorbed in the colon and converted to its pharmacologically active form of 5-amino 5-salicylic acid by azoreductase in gut microbiota 32 , 33 . FLZ is a novel synthetic derivative of squamosamide for the treatment of PD.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that more than 30 commonly prescribed drugs were metabolically altered by the enzymes in gut microbiota 24 , 25 , 26 , including methylase/demethylase, β -glucuronidase, nitroreductase, azoreductase, and so on 27 , 28 , 29 , 30 , 31 . For example, sulfasalazine, a sulfa drug used for the treatment of ulcerative colitis, is absorbed in the colon and converted to its pharmacologically active form of 5-amino 5-salicylic acid by azoreductase in gut microbiota 32 , 33 . FLZ is a novel synthetic derivative of squamosamide for the treatment of PD.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative coupling of benzaldehyde with o-aminophenol utilizing lead tetraacetate represents one of these synthetic methods. Although it is not among the popular OD Sample Percentage of Cell Viability = ññññññññññññ × 100 1OD Control methods, possibly due to the oxidative power of lead tetraacetate (14,15). It is reported that lead tetraacetate can cause oxidative decarboxylation of organic carboxylic compounds (16).…”
Section: Synthetic Chemistrymentioning
confidence: 99%
“…The urea linkages are cleaved by ureases generated by bacteria delivering the antibiotic, enhancing the efficacy and minimizing side effects (Xu et al, 2013). Another bacteria-generated enzyme that may be used with this purpose is the azoreductase, but, to date, the introduction of azo moieties has only been employed in the design of prodrugs (Jilani et al, 2013) and on a dual responsive system that will be described later.…”
Section: Enzyme-responsive Polymersmentioning
confidence: 99%